1997
DOI: 10.1038/bjc.1997.501
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptors and anti-proliferative effects of vitamin D derivatives in human pancreatic carcinoma cells in vivo and in vitro

Abstract: Summary The GER human pancreatic carcinoma cell line possesses receptors for 1,25-dihydroxyvitamin D3. We report that the vitamin D analogue EB 1089 inhibits the growth of these cells in vitro and when grown as tumour xenografts in immunodeficient mice. Tumour-bearing mice were given EB 1089 at a dose of 5 gg kg-' body weight i.p. thrice weekly for 4-6 weeks. Tumour growth was significantly inhibited in treated animals compared with controls in the absence of hypercalcaemia. These findings may have therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
68
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 21 publications
(19 reference statements)
1
68
0
1
Order By: Relevance
“…Differential effects have also been shown in melanoma and colon cancer cells (Kane et al, 1996;Danielsson et al, 1999). In pancreatic cancer cells, responsiveness to both retinoids and vitamin D analogues have been reported previously (Rosewicz et al, 1995;Bold et al, 1996;Kawa et al, 1996;Louvet et al, 1996;Zugmaier et al, 1996;Colston et al, 1997). However, those studies have mainly assessed inhibition of cell growth and apoptosis has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential effects have also been shown in melanoma and colon cancer cells (Kane et al, 1996;Danielsson et al, 1999). In pancreatic cancer cells, responsiveness to both retinoids and vitamin D analogues have been reported previously (Rosewicz et al, 1995;Bold et al, 1996;Kawa et al, 1996;Louvet et al, 1996;Zugmaier et al, 1996;Colston et al, 1997). However, those studies have mainly assessed inhibition of cell growth and apoptosis has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Most pancreatic cancer cells express the vitamin D receptor (VDR) (Kawa et al, 1996;Colston et al, 1997) as well as receptors for the retinoic acids (Rosewicz et al, 1995), suggesting that these cells may respond to treatment with these agents.…”
mentioning
confidence: 99%
“…In vivo studies in animal models have shown that seocalcitol can cause regression of established tumours, prevent the development of metastases, and prolong survival time in tumour-bearing animals (Colston et al, 1992(Colston et al, , 1997James et al, 1998;Lokeshwar et al, 1999;Nickerson and Huynh, 1999), with significant inhibition of tumour progression achieved at doses that do not cause significant hypercalcaemia (Colston et al, 1992). Furthermore, seocalcitol inhibits growth of pancreatic cancer cells in vitro (Zugmaier et al, 1996;Pettersson et al, 2000) and inhibits growth in vivo of pancreatic cancer xenografts in immunodeficient mice (Colston et al, 1997). Seocalcitol was well tolerated in a phase I clinical study in patients with breast or colorectal cancer, with dose-dependent hypercalcaemica (Gulliford et al, 1998).…”
mentioning
confidence: 99%
“…Seocalcitol is a differentiating agent which has shown promise in animal models of cancer (Akhter et al, 1997;Colston et al, 1997a;Lokeshwar et al, 1999). Previous studies with this vitamin D analogue in breast and colorectal cancer (Gulliford et al, 1998) and pancreatic cancer (Evans et al, 2002) have not demonstrated any evidence of antitumour activity as determined by objective reduction in tumour volume.…”
Section: Discussionmentioning
confidence: 99%
“…In tumour-bearing animals, Seocalcitol has been shown to suppress growth of chemically induced breast cancer (James et al, 1998) and xenografts of colon cancer (Akhter et al, 1997), breast cancer (Colston et al, 1992) and pancreatic cancer (Colston et al, 1997a), and to inhibit metastasis from prostate cancer (Lokeshwar et al, 1999). Vitamin D receptors have been reported to be present in the liver including human hepatocytes (Berger et al, 1988).…”
mentioning
confidence: 99%